Early childhood stress is associated with blunted development of ventral tegmental area functional connectivity - Park, Anne T.; Tooley, Ursula A.; Leonard, Julia A.; Boroshok, Austin L.; McDermott, Cassidy L.; Tisdall, M. Dylan; Mackey, Allyson P. (Developmental cognitive neuroscience, 2021)
•Age-related changes in VTA-mPFC connectivity are moderated by SES and early adversity.•Connectivity between the VTA and caudate increases with age in childhood.•Findings are consistent with rodent models showing stress susceptibility in the VTA.•Stress exposure may blunt the development of reward circuitry in childhood. Early life stress increases risk for later psychopathology, due in part to changes in dopaminergic brain systems that support reward processing and motivation. Work in animals has shown that early life stress has a profound impact on the ventral tegmental area (VTA), which provides dopamine to regions including nucleus accumbens (NAcc), anterior hippocampus, and medial prefrontal cortex (mPFC), with cascading effects over the course of development. However, little is known about how early stress exposure shifts the developmental trajectory of mesocorticolimbic circuitry in humans. In the current study, 88 four- to nine-year-old children participated in resting-state fMRI. Parents completed questionnaires on their children's chronic stress exposure, including socioeconomic status (SES) and adverse childhood experiences (ACEs). We found an age x SES interaction on VTA connectivity, such that children from higher SES backgrounds showed a positive relationship between age and VTA-mPFC connectivity. Similarly, we found an age x ACEs exposure interaction on VTA connectivity, such that children with no ACEs exposure showed a positive relationship between age and VTA-mPFC connectivity. Our findings suggest that early stress exposure relates to the blunted maturation of VTA connectivity in young children, which may lead to disrupted reward processing later in childhood and beyond.